Smart wearable devices for real-time health monitoring - Ruby Dhar; Kumar, Arun; Subhradip Karmakar (Asian Journal of Medical Sciences, 2023)
Smartwatches have emerged as powerful tools for health monitoring in recent years. These wearable devices combine advanced technology with portability, enabling individuals to track various aspects of their health and well-being conveniently. Heart rate monitoring has several advantages. Many smartwatches are equipped with optical heart rate sensors that continuously monitor a user’s heart rate. This feature provides real-time data on heart rate variations, which can be crucial for identifying irregularities and assessing overall cardiovascular health. Activity tracking: Smartwatches often include accelerometers and gyroscopes that track physical activities such as steps taken, distance traveled, and calories burned. This information can aid in setting and achieving fitness goals. Sleep tracking:Some smartwatches offer sleep tracking features, recording sleep duration, quality, and patterns. These data help users understand their sleep habits and make improvements for better rest. Global positioning system (GPS) and location tracking: Integrated GPS allows users to track their outdoor activities accurately, including running and cycling. This feature not only measures performance but also enhances safety during workouts. Stress monitoring: Certain smartwatches include tools that measure stress levels through heart rate variability analysis. Users can learn to manage stress more effectively based on these data. Electrocardiogram (ECG) and blood pressure monitoring:High-end smartwatches may include ECG and blood pressure monitoring capabilities. These features are particularly useful for individuals with heart conditions or hypertension. Notifications and alerts: Smartwatches can deliver notifications and alerts related to health goals, reminders to move, medication schedules, and emergencies. This functionality enhances user engagement and timely interventions. BENEFITS OF SMARTWATCHES IN HEALTH MONITORING Unlike periodic doctor visits, smartwatches enable continuous health monitoring. Users can track their vital signs and activities throughout the day, providing a more comprehensive picture of their health. Smartwatches empower individuals to take control of their health. Users can make informed decisions about their lifestyle, exercise, and diet by providing real-time data. Smartwatches equipped with ECG and heart rate monitoring can detect irregularities and abnormalities early on. This early detection can be lifesaving for individuals at risk of heart-related conditions. Activity tracking and goal-setting features motivate users to engage in physical activities and maintain a healthier lifestyle. Achieving fitness goals can lead to increased motivation and adherence to healthier habits. Health data collected by smartwatches can be used to tailor fitness and wellness plans to an individual’s specific needs. This personalized approach can lead to more effective health improvements. LIMITATIONS AND CONSIDERATIONS Accuracy: While smartwatches offer valuable health data, their accuracy may vary. Factors such as skin type,device placement, and motion can affect the precision of measurements. Battery life: Continuous health monitoring can drain a smartwatch’s battery quickly. Users may need to recharge their devices frequently, potentially limiting the monitoring duration. Privacy and data security: Storing sensitive health data on a smartwatch raise concerns about privacy and data security. Manufacturers must implement robust security measures to protect users’ information. User reliance: There is a risk of over-reliance on smartwatches for health information. Users should be encouraged to consult health-care professionals for a comprehensive health assessment. CONCLUSION Smartwatches have become versatile tools for health monitoring, offering a range of features that empower users to track and improve their well-being. While they have numerous benefits, users should know their limitations and use them as complementary tools in their health-care journey. Manufacturers and health-care providers play a critical role in ensuring the accuracy and security of the health data collected by these devices.